A Mapping the Distribution and Accessibility of Midwifery Practices in Jembrana Regency in 2025 Using a Geographic Information System (GIS) - I Gusti Ayu Putu Gita Anjani Putri; Ketut Hari Mulyawan (Primary Care Science and Practice (PCSP), 2026)
Background: Midwives play an important role in the implementation of antenatal care (ANC). However, disparities in the distribution of midwifery practices remain a significant issue. The distribution of midwifery practices in Jembrana Regency is still uneven. Objective: This study aims to analyze the distribution patterns and accessibility of midwifery practices in Jembrana Regency in 2025 using a Geographic Information System (GIS) approach. Methods: This study employed a cross-sectional spatial analysis using Geographic Information Systems (GIS) to examine the distribution patterns and geographical accessibility of midwifery practices and was conducted in Jembrana Regency from December 2025 to January 2026. The sample was selected using the total sampling method. Data analysis was carried out using Microsoft Excel and a Geographic Information System (GIS)-based application. Results: There are 458 midwifery practices in 91 locations, with 229 (50%) located in puskesmas. The distribution pattern is clustered, with hot spots at a 99% confidence level in Jembrana and Negara Sub-districts. The average distance from village centers to the nearest practice is 894,25 meters, with the shortest distance 32,50 meters. Two practice locations were not recorded by Dinas Kesehatan and Dinas PMPTSP of Jembrana Regency. Conclusion: The government needs to develop a needs-based distribution planning strategy for midwifery practices in each region to support equitable access to services.